ChemInform Abstract: Enantioselective Syntheses of Indanes: From Organocatalysis to C—H Functionalization. Issue 17 (April 2016) - Borie, Cyril; Ackermann, Lutz; Nechab, Malek
Abstract: Review: [144 refs.